2012
DOI: 10.4314/bajopas.v5i1.18
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Growth, Organs Weight and Haematological Parameters of Broiler Chicken Fed Graded Level of Sun Dried Cassava Root Meal

Abstract: Ninety (90) day old broiler chicks were used to investigate the response of broilers fed sun-dried cassava root meal (CRM). Five diets at starter and finisher phases in which CRM replaced maize at 0, 25, 50, 75 and 100% and designated T1, T2, T3, T4 and T5 respectively. Diets were allocated to day old broiler chicks in a completely randomized design (CRD). Birds were raised on dip-litter system and the experiment lasted for eight (8) weeks. Feed intake was taken daily, while body weights were recorded weekly. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 3 publications
(2 reference statements)
2
4
0
Order By: Relevance
“…Also, the feed intake of birds fed sun dried CSB decreased significantly as the inclusion level of cassava increased at both starter and finisher phases. This is as well in line with the findings of Hassan et al (2012) who fed broiler chickens graded levels of sun-dried cassava root meal. The best FCR was observed in the birds fed dry heated soya beans in fried CSB at 80:20 inclusion ratios (CDF ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Also, the feed intake of birds fed sun dried CSB decreased significantly as the inclusion level of cassava increased at both starter and finisher phases. This is as well in line with the findings of Hassan et al (2012) who fed broiler chickens graded levels of sun-dried cassava root meal. The best FCR was observed in the birds fed dry heated soya beans in fried CSB at 80:20 inclusion ratios (CDF ).…”
Section: Discussionsupporting
confidence: 90%
“…Feed intake decreased as the level of inclusion of cassava increased at the finisher phase, and was lowest for blends containing 80:20 mixing ratio of CSB. This could be an indication of the adequate energy contents of these diets as birds feed to satisfy their energy requirements, as this agrees with the findings of Hassan et al (2012) and that of Ukachukwu (2005) who reported a significant difference in daily feed intake of birds when cassava root meal was fed. Omekan (1994) also reported a drop in feed intake of birds fed cassava leaf meal which could be due to the fact that the leaf meal imparted unpalatable taste to the feed which consequently inhibited the birds from consuming adequate quantities.…”
Section: Discussionsupporting
confidence: 90%
“…There was however, 8.5% decrease (P>0.05) in feed intake of birds fed the diet containing the cassava flour. In contrast, Ukachukwu (2005) and Hassan et al (2012) also reported a decline in feed intake of birds fed cassava-based diets, and this negative effect was increased as the inclusion level of the cassava in the diet increased. This could have also been due to the dusty nature of the cassava flour.…”
Section: Resultsmentioning
confidence: 97%
“…All the assessed haematological parameters including WBC, RBC, HB, MCH, MCHC, HCT, and MCV were within the reference range of healthy birds (Campbell et al, 2003). Unigwe (2011) and Hassan et al (2012) reported no detrimental effect on blood haematology parameters when cassava meal was fed to broiler chickens.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation